O processo de desconcentração regional da indústria brasileira no período recente - Santos, Wesley Oliveira (2013)
This study aimed to identify the default location of industrial activity in Brazil in the period between 1995 and 2009, establishing a profile of the changes in the regional distribution of industry, so check the assertiveness of some of the trends identified in the literature Empirical domestic regional development in the debate established until the late 1990s. For this reason, information on the distribution of industrial GDP, industrial employment and the number of industrial establishments in the regions and states of Brazil, were treated by descriptive analysis of the holdings of the regions and federal units in the country's total and calculation and analysis of indices of concentration and specialization, such as the Concentration Ratio and its derivation in the form of Curves Concentration, Quotient Locational and Herfindahl-Hirschman Index. The results indicate the continuing process of industrial decentralization in Brazil under interregional lower intensity, but not too dissimilar to what was witnessed in the country throughout the 1970s and until the mid 1980s. This movement was due to the loss of market share in the Southeast in favor of other regions, among which the Midwest and Northeast stand out among the most dynamic in all the analyzes of the three variables of interest. In this sense, except that the tendency to "fragmentation of the national economy" was not corroborated the results keep closer to the prognosis made by Pacheco (1996 and 1999) and Guimarães Neto (1995 and 1997) than in relation to prognosis of refocusing around the metropolitan region of São Paulo Cano (1998) and polygonal reconcentration observed in Diniz (1993), as a function of the observed changes over time in some of the determinants mentioned by the latter, which allowed to explain so more appropriate devolution and its future trends from the perspective of the principle of circular and cumulative causation of Myrdal, when considering the influence of the recent improvement in income distribution on the expansion and dissemination of the domestic consumer market.